1985
DOI: 10.1557/proc-51-349
|View full text |Cite
|
Sign up to set email alerts
|

The Crystalline-To-Amorphous Phase Transition In Irradiated Silicon

Abstract: The amorphous(a)-to-crystalline (c) phase transition has been studied in electron(e-) and/or ion irradiated silicon (Si). The irradiations were performed in i n the Argonne High Voltage Microscope-Tandem Facility The irradia ion of Si, at <10 K, with 1-MeV e- to a fluence of 14 dpa failed to induce the c-to-a transition. Whereas an irradiation, at <10 K, with 1.0 or 1.5-MeV Kr+ ions induced the c-to-a transition by a fluence of ≈0.37 dpa. Alternatively a dual irradiation, at 10 K, with 1.0-MeV e and 1.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A Faraday cup located above the specimen position was used to measure total beam current (I T ) , and a movable Faraday cup located in the viewing chamber was used for beam profiling and for measuring the peak electron flux (I P ) . Typical beam profiles employed for this study can be described approximately by a Gaussian distribution, I(r) = I p -exp{-1/2(r/a) 2 } [1]• The parameter a is the standard deviation of the distribution, and was calculated from the measured electron fluxes using the relationship O-(I T /27tI P ) l / 2 . The beam parameters were chosen to obtain a peak electron flux of 2 x 10 19 electrons/cm 2 /s, corresponding to a calculated peak displacement rate of 1 x 10" 3 dpa/s.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Faraday cup located above the specimen position was used to measure total beam current (I T ) , and a movable Faraday cup located in the viewing chamber was used for beam profiling and for measuring the peak electron flux (I P ) . Typical beam profiles employed for this study can be described approximately by a Gaussian distribution, I(r) = I p -exp{-1/2(r/a) 2 } [1]• The parameter a is the standard deviation of the distribution, and was calculated from the measured electron fluxes using the relationship O-(I T /27tI P ) l / 2 . The beam parameters were chosen to obtain a peak electron flux of 2 x 10 19 electrons/cm 2 /s, corresponding to a calculated peak displacement rate of 1 x 10" 3 dpa/s.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study [1] has shown that amorphization of Si during irradiation with 1-MeV Kr + icns at 10 K can be strongly retarded by simultaneously irradiating the sample with a 1-MeV electron beam. The retardation effect under simultaneous irradiation was found to occur only when the calculated electron displacement rate (dpa/s) exceeded that for the Kr + beam by a factor of about two.…”
Section: Introductionmentioning
confidence: 99%